Development of Guidance and Counseling Teachers and its Implications in Educational Management - Elvia Kurniawati; Neviyarni S; Yarmis Sukur (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Guidance and Counseling teacher development is an effort to improve the technical, theoretical, conceptual, and moral abilities of Guidance and Counseling teachers according to job/position needs through education and training. As a professional, BK teachers require expertise, skills, or abilities that have certain quality standards or norms and require professional education in carrying out their duties and responsibilities. Teachers, both individually and in groups, need to always improve the quality and dignity of their profession. In order to improve quality, both professional quality and service quality, teachers must also improve their professional attitudes. The purpose of this study was to determine the Development of Guidance and Counseling Teachers and Its Implications in Education Management. The research method is This study uses a qualitative descriptive approach with a case study research type. Qualitative methods are used to understand the meaning of social or humanitarian problems that are considered important by a group of people. The results of this study are that pedagogical skills must also be possessed by Guidance and Counseling teachers. The main target of developing guidance teachers is to achieve academic qualification standards and counselor competencies in counseling services in schools.